The effectiveness of smartphone applications as an effort to improve cardiopulmonary resuscitation (CPR) : Literatur review - Aris Nur Rahmat; Ridlwan Kamaluddin (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background : Cardiac arrest is a life-threatening emergency. Cardiac arrest must immediately get fast and appropriate treatment through the provision of Cardio Pulmonary Resuscitation (CPR). Doing CPR requires mental and knowledge. Material knowledge is obtained from media that is easily accessible to anyone, such as applications that contain CPR on smartphones.Objectives : To analyze and assess the quality of articles about the effectiveness of smartphone applications as an effort to improve cardiopulmonary resuscitation (CPR).Methods : Article search using the Pubmed and Science Direct electronic databases. The search for articles used was the last 10 years with the keywords “Telenursing OR Telehealth OR Smartphone”, AND “Cardiopulmonary OR Cardiac Arrest”.Results : Results 6 of 13 articles applied the research design with RCTs, the other articles applied retrospective, prospective observation studies, and A mixed-methods evaluation study. The results of the article review show that smartphone feature functions include reports of cardiac arrest cases and learning-based applications regarding CPR. 1 of 13 articles describes the function of the report feature via SMS base system notification. Other articles discuss CPR learning features with video conferencing audio telephone calls instruments, Resusci Anne Skillreporter manikin, Laerdal skillreporting system V.2.2.1 software, use of U-CPR, The VADSS software application, Laerdal resusci-anne simulator, A SimMan simulator (Laerdal, Stavanger, Norway) and cardiac arrest simulation test score, guidelines for basic life support suitability test and system usability scale (SUS), video instructions for Dispatcher-assisted CPR and CPR quality, and CPR manikins and resuscitation council (UK)-endorsed lifesaver VR.Conclusions : Smartphones have been well developed and used in providing CPR by countries that have developed information systems. In addition, the smartphone feature can improve the quality of CPR, provide layperson CPR, and speed up CPR access. However, further research is needed to ensure the quality of the smartphone and the communication systems that support it so that there is no delay in administering CPR